The Resurrection of the Body and the Life Everlasting - Whale, J. S. (Scottish journal of theology, 1949)
The golden ripple on the wall came back again, and nothing else stirred in the room. The old, old fashion! The fashion that came in with our first garments, and will last unchanged until our race has run its course, and the wide firmament is rolled up like a scroll. The old, old fashion—Death!